Aardman animations ([S.l.] : Connoisseur Video, 1991)
Specialising in plasticine and model animation, the Aards have demonstrated just how imaginatively this form of animation can be used, bringing their characters to life via vivid observational detail and idiosyncratic touches of humour
The video includes Oscar winning Creature comforts and award winning TV commercials Heat electric
Keywords: Animated films